PERAN KOPERTAIS IX DALAM PEMBINAAN MUTU PERGURUAN TINGGI AGAMA ISLAM DI SUMATERA UTARA: THE ROLE OF KOPERTAIS REGION IX IN THE QUALITY DEVELOPMENT OF ISLAMIC HIGHER EDUCATION INSTITUTIONS IN NORTH SUMATERA - Ibnu Salman (Penamas, 2014)
Koordinatoriat Perguruan Tinggi Agama Islam Swasta (Coordinator for Private Islamic Higher Education, Kopertais) has an important role in developing and improving the quality of Islamic Higher Education Institutions. This article presents the results of research on the capacity of Kopertais Region IX in developing the quality Islamic higher education institutions in North Sumatera. The research used a qualitative approach. Interviews, observations, questionnaires, and documentation were employed for data collection. One of the important findings is that Kopertais Region IX suffers a institutional weakness because it is included in the organization of IAIN (State Institute for Islamic Studies) North Sumatera, as part of IAIN’s Institutional Cooperation Section. The Rector of IAIN North Sumatera also acts as the Head of Kopertais Region IX. The author of this article argues that this institutional dependency causes Kopertais Region IX less performed in developing the quality of private Islamic higher education in North Sumatera. Key words: Kopertais Region IX, private Islamic higher education, quality, IAIN North Sumatera. Koordinatoriat Perguruan Tinggi Agama Islam Swasta (Kopertais) sesungguhnya memainkan peran penting dalam pembinaan mutu di Perguruan Tinggi Agama Islam, namun sayangnya hal ini belum mendapat perhatian dalam penelitian. Penelitian ini dilakukan di Provinsi Sumatera Utara dan mencoba melihat kapasitas kelembagaan Kopertais IX dalam pembinaan PTAIS yang berkualitas. Penelitian ini menggunakan pendekatan kualitatif dan bersifat deskriptif, menggunakan teknik wawancara, observasi, kuesioner, dan dokumentasi. Penelitian ini menunjukkan, bahwa secara umum Kopertais IX termasuk dalam struktur (Organisasi Tata Kerja Pegawai) IAIN Sumatera Utara termasuk sub PTAIS bagian dari kelembagaan kerjasama dan menunjukkan secara struktural lemah dalam pijakan kebijakannya. Kinerja Kopertais IX dalam pembinaan mutu PTAIS di Sumatera Utara belum maksinal/lemah akibat terkendala karena masih di bawah struktur IAIN Sumatera Utara, bukan sebagai lembaga independen dan koordinator Kopertais sekaligus merangkap sebagai Rektor IAIN Sumatera Utara. Kata Kunci: Kopertais wilayah IX, mutu, Perguruan Tinggi Agama Islam Swasta (PTAIS).